From the individual to the colony: Marine invertebrates as models to understand levels of biological organization. Issue 3 (5th April 2021) - Hiebert, Laurel S.; Vieira, Leandro M.; Tiozzo, Stefano; Simpson, Carl; Grosberg, Richard K.; Migotto, Alvaro E.; Morandini, Andre C.; Brown, Federico D.
Abstract: The developmental and evolutionary principles of coloniality in marine animals remain largely unexplored. Although many common traits have evolved independently in different groups of colonial animals, questions about their significance for colonial life histories remain unanswered. In 2018 (Nov. 25 ‐ Dec. 8), the inaugural course on the Evolution of Coloniality and Modularity took place at the Center for Marine Biology of the University of São Paulo (CEBIMAR‐USP), Brazil. During the intensive two‐week graduate‐level course, we addressed some of the historical ideas about animal coloniality by focal studies in bryozoans, tunicates, cnidarians, and sponges. We discussed many historical hypotheses and ways to test these using both extant and paleontological data, and we carried direct observations of animal colonies in the different phyla to address questions about coloniality. We covered topics related to multi‐level selection theory and studied colonial traits, including modular miniaturization, polymorphism, brooding, and allorecognition. Course participants carried out short research projects using local species of animals to address questions on allorecognition and regeneration in ascidians and sponges, fusion and chimerism in anthoathecate hydrozoans, and evolution of polymorphism in bryozoans. Although many questions remain unanswered, this course served as a foundation to continue to develop a developmental and evolutionary synthesis of clonal and modular development in colonial marine organisms. Abstract :